2022
DOI: 10.1021/acs.cgd.2c00153
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electronic Properties and Interaction Landscapes in a Series of N-(Chlorophenyl)pyridinecarboxamides

Abstract: A 3 × 3 isomer grid of nine N -(chlorophenyl)pyridinecarboxamides ( NxxCl ) is reported with physicochemical studies and single crystal structures ( Nx = pyridinoyl moiety; xCl = aminochlorobenzene ring; x = para -/ meta -/ ortho -), as synthesized by the reaction of the substituted p -/ m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 120 publications
0
1
0
Order By: Relevance
“…amide interaction is less notable (N c values ≥ 0.90). In tandem, the R In previous studies of 3 × 3 isomer grids, we reported detailed analyses of their melting points and examined the influence of the substituent position and molecular symmetry [17][18][19]40]. The X-DIP series with six compounds shows a melting point trend increasing along the series from H→F→Cl→Br→I→NO 2 , noting Z' = 3 for Cl-DIP and hemihydrate in I-DIP• 1 /2(H 2 O).…”
Section: Crystallographic Structural Summarymentioning
confidence: 99%
“…amide interaction is less notable (N c values ≥ 0.90). In tandem, the R In previous studies of 3 × 3 isomer grids, we reported detailed analyses of their melting points and examined the influence of the substituent position and molecular symmetry [17][18][19]40]. The X-DIP series with six compounds shows a melting point trend increasing along the series from H→F→Cl→Br→I→NO 2 , noting Z' = 3 for Cl-DIP and hemihydrate in I-DIP• 1 /2(H 2 O).…”
Section: Crystallographic Structural Summarymentioning
confidence: 99%
“…Given the high similarity in electron-density properties (Gallagher et al, 2022) between a compound interacting with the active site of a protein in the biological environment and its crystalline state (Zhurova et al, 2009), an electron-density study was initiated on monascin in its crystalline state to explore its molecular structure (Shyni et al, 2021). Experimental electron-density studies of monascin are conducted by utilizing atomic parameters from the Experimental Library of Multipolar Atom Model 2 (ELMAM2) database (Bibila Mayaya Bisseyou et al, 2012), which is based on optimal local coordinate systems (Domagała & Jelsch, 2008), due to the absence of high-resolution diffraction data.…”
Section: Introductionmentioning
confidence: 99%